Fermentation of Plant-Based Feeds with Lactobacillus acidophilus Improves the Survival and Intestinal Health of Juvenile Nile Tilapia (Oreochromis niloticus) Reared in a Biofloc System - Neves N.O.D.S.* (2024)
© 2024 by the authors.This study evaluated the effect of fermentation with Lactobacillus acidophilus on the biochemical and nutritional compositions of a plant-based diet and its effects on the productive performance and intestinal health of juvenile Nile tilapia (Oreochromis niloticus) reared in a biofloc technology (BFT) system. The in vitro kinetics of feed fermentation were studied to determine the L. acidophilus growth and acidification curve through counting the colony-forming units (CFUs) mL−1 and measuring the pH. Physicochemical and bromatological analyses of the feed were also performed. Based on the microbial growth kinetics results, vegetable-based Nile tilapia feeds fermented for 6 (FPB6) and 18 (FPB18) h were evaluated for 60 days. Fermented diets were compared with a positive control diet containing fishmeal (CFM) and a negative control diet without animal protein (CPB). Fermentation with L. acidophilus increased lactic acid bacteria (LAB) count and the soluble protein concentration of the plant-based feed, as well as decreasing the pH (p < 0.05). FPB treatments improved fish survival compared with CPB (p < 0.05). Fermentation increased feed intake but worsened feed efficiency (p < 0.05). The use of fermented feeds increased the LAB count and reduced pathogenic bacteria both in the BFT system’s water and in the animals’ intestines (p < 0.05). Fermented plant-based feeds showed greater villi (FPB6; FPB18) and higher goblet cell (FPB6) counts relative to the non-fermented plant-based feed, which may indicate improved intestinal health. The results obtained in this study are promising and show the sustainable potential of using fermented plant-based feeds in fish feeding rather than animal protein and, in particular, fishmeal.